PENGARUH METODE DISKUSI KELOMPOK KECIL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PPKn KELAS VIII SMP IT AL- FITYAH PEKANBARU - Purba, Nuraina; Supentri, Supentri; Primahardani, Indra (Komunitas Manajemen Kompetitif, 2024)
The aim of this research is to examine whether there is an influence of the small group discussion method on students' critical thinking skills in the Civics Class VIII SMP IT Al-Fityah subject. This research is experimental research using a quantitative approach. The population in this study was 51 students, where samples were taken randomly (drawing lots), namely two classes were taken to become the experimental class (VIII B) with 25 students and the control class (VIII A) with 26 students. The data collection instruments used were questionnaires, observations and data processing documentation using the help of IBS SPSS. This research analysis uses prerequisite tests, namely descriptive analysis, normality test, homogeneity test, T test, and N-Gain test. The results of the T test show that the value of Fcount > Ftable or 2.418 > 1676. So Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of the small group discussion method on students' critical thinking skills. The N-Gain test obtained in the experimental class was 65.54% in the quite effective category, while in the control class it was 51.39% in the less effective category. Keywords :